Kinetic Study of The Oxidation of Pentaaminecobalt(III) Complexes of α-hydroxy Acids by Imidazolium Dichromate - Sankaran, K.R.; Anbuselvan, C. (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of pentaamminecobalt(Ill) complexes of mandelic and lactic acids by imidazoliurn dichromate (IDC) have been studied in the presence of 1.00 mol dm-3 HCIO4. The rates of oxidation show first order kinetics each in Co(III) complex and [IDC]. Various thermodynamic parameters have been evaluated.The stoichiometry of the reaction has been determined. The fonnationof keto acid Co(III) complex as the product of the reaction isaccounted by a suitable mechanism.